Randomised clinical trial: comparison of two everolimus dosing schedules in patients with advanced hepatocellular carcinoma. Issue 1 (8th November 2012) - Shiah, H.‐S.; Chen, C.‐Y.; Dai, C.‐Y.; Hsiao, C.‐F.; Lin, Y.‐J.; Su, W.‐C.; Chang, J.‐Y.; Whang‐Peng, J.; Lin, P.‐W.; Huang, J.‐D.; Chen, L.‐T.
Summary Background Deregulation of mammalian target of rapamycin (mTOR) signalling is common in human hepatocellular carcinoma (HCC). Aim To determine the maximum tolerated dose (MTD) of the oral mTOR inhibitor everolimus in advanced HCC patients. Methods Patients with locally advanced or metastatic HCC (Child‐Pugh class A or B) were enrolled in an open‐label phase 1 study and randomly assigned to daily (2.5–10 mg) or weekly (20–70 mg) everolimus in a standard 3 + 3 dose‐escalation design. MTD was based on the rate of dose‐limiting toxicities (DLTs). Secondary endpoints included safety, pharmacokinetics and tumour response. In a post hoc analysis, serum hepatitis B virus (HBV) DNA levels were quantified. Results Thirty‐nine patients were enrolled. DLTs occurred in five of 21 patients in the daily and two of 19 patients in the weekly cohort. Daily and weekly MTDs were 7.5 mg and 70 mg respectively. Grade 3/4 adverse events with a ≥10% incidence were thrombocytopenia, hypophosphataemia and alanine transaminase (ALT) elevation. In four hepatitis B surface antigen (HBsAg)‐seropositive patients, grade 3/4 ALT elevations were accompanied by significant (>1 log) increases in serum HBV levels. The incidence of hepatitis flare (defined as ALT increase >100 IU/mL from baseline) in HBsAg‐seropositive patients with and without detectable serum HBV DNA before treatment was 46.2% and 7.1% respectively (P < 0.01, Fisher exact test). Disease control rates in the daily and weekly cohorts were 71.4% and 44.4% respectively. Conclusions The recommended everolimus dosing schedule for future hepatocellular carcinoma studies is 7.5 mg daily. Prophylactic anti‐viral therapy should be mandatory for HBsAg‐seropositive patients (ClinicalTrials.gov NCT00390195).